Optimalisasi Pendapatan Berkendala Pada Usaha Mi Bakso Di Kota Metro - Riza Ardila; Emi Maimunah (CV. Multi Kreasi Media, 2023)
One of the goals of a company is to maximize the revenue that can be achieved through the combination of production quantities for each product. This study aims to determine whether the production combination of each type of meatball noodle product has reached optimal revenue. The data used in this research are primary and secondary data. The respondents in this research are meatball noodle business owners in Central Metro Subdistrict, selected using purposive sampling technique. This research method is quantitative, calculating the revenue optimization of product combinations. The analytical tool used is Linear Programming with the simplex method, and the software used is POM-QM for Windows 3. The calculation results show that the established production combination and revenue obtained by the meatball noodle business in Metro City are not yet optimal. The optimal revenue level is Rp 8,229,938.00 with a production combination of 281 units of large meatball noodles and 202 units of small meatball noodles.